Chingu Topokki & Chingu Gochu by TOPOKKIYOWO / Nursyahirah Razaman and Nur Anisya Nabihah Mohd Akmaluddin - Razaman, Nursyahirah; Mohd Akmaluddin, Nur Anisya Nabihah (2022)
Topokkiyowo is a trademark for our Chingu Topokki and Chingu Gochu. The main objective is to offer a variety of Halal Instant Tteokbokki from Korea to our customers with affordable prices and luxurious tastes of Korea. Our business was started in October 2021. According to the customer review, our products give a great taste because the taste of chewiness and spiciness on Chingu Topokki and Chingu Gochu leaves an unforgettable taste for them. As an agent of Chingu Malaysia HQ, we are happy with their good feedback toward our product. Other than it is easy to cook because it only takes around seven minutes to cook, this product is also favored because it is cheap and affordable price for them to try and repeat buying it again. Hence, this product provides a good insight for the continuation of sale to our customers. Since early of its opening, Chingu Topokki and Chingu Gochu by Topokkiyowo was sold more than 30 packages with different flavors. The increasing demands for our product result in a good profitable sale revenue to our business. Therefore, Chingu Topokki and Chingu Gochu by Topokkiyowo is a good marketable product of choice that can be further expanded to many different areas as the business keeps on growing.